THE ROLE OF USTU IN THE ORGANIZATION AND DEVELOPMENT OF NETWORKING COOPERATION IN EDUCATIONAL SPACE OF KOMI REPUBLIC - Nikolay D. Tskhadaya (Высшее образование в России)
The article analyzes the activity of USTU as a source of development of common educational space of Komi Republic and views three main lines of university activities: education, science and research, sociocultural mission. The author especially considers the prospects of networking cooperation between USTU and schools of the city of Ukhta as a pivotal city of the Komi Republic.